PENGEMBANGAN BLENDED LEARNING DENGAN MODEL FLIPPED CLASSROOM - Sutisna, M. Ridwan; Mulyadi, Dadi; Alinawati, Muthia (PEDAGOGIA, 2019)
AbstrakPengembangan pembelajaran dengan melibatkan teknologi menjadi salah satu dampak pesatnya perkembangan teknologi. Blended learning menjadi salah satu opsi yang dapat diadaptasi, namun upaya pengembangan pembelajaran menggunakan blended learning masih belum masif. Penelitian ini mencoba untuk mengembangkan salah satu model desain pembelajaran menggunakan metode penelitian Design and Development (DnD). Hasil dari penelitian ini yaitu model GALE yang dapat digunakan untuk mengembangkan pembelajaran menggunakan strategi blended learning. Model GALE merupakan turunan yang dikembangkan dari model instruksional ADDIE, memiliki empat tahapan yaitu Goal Analysis, Activity Plan, Learning Resources Development, dan Evaluate and Reflection. Dalam penerapannya, blended ini dilakukan di mata kuliah penelitian dan pengembangan teknologi pendidikan pada semester tujuh di program studi teknologi pendidikan. Sekaligus smemanfaatkan fasilitas learning management system yang dimiliki oleh UPI yaitu spot.upi.edu. Hasil dari pengembangan pembelajaran ini dapat menunjang pembelajaran sesuai dengan kebutuhan blended learning yang telah dikembangkan. Selain itu, penelitian ini diharapkan mampu memberikan best practice pengembangan blended learning, selain juga menyajikan model GALE sebagai alternatif model pengembangannya.Â AbstractThe development of instruction involving technology is one of the effects of the technology rapid development. Blended learning strategy is an option that can be adapted for instructions. However, efforts to develop instruction using blended learning are still not massive enough. This study tries to develop one of the learning design models using the Design and Development (DnD) research method. The results of this study are GALE models that can be used to develop learning using the blended learning strategy. The GALE model is a derivative developed from the ADDIE instructional model. It has four stages, start with the Goal Analysis, Activity Plan, Learning Resources Development, and Evaluate and Reflection. In its implementation, this instructional design model for blended learning strategy is carried out in the research and development of educational technology courses in the seventh semester in Educational Technology program. While at the same time utilizing the Learning Management System (LMS) facility owned by UPI, namely spot.upi.edu. The results of developing this instructional design model can support learning appropriately match to the blended learning needs that have been developed. In addition, this research is expected to be able to provide best practice for the development and implementation of blended learning strategy, and also to presenting the GALE model as an alternative development model.